Case of low dose clenbuterol toxicity - Waight, Michael (BMJ Case Rep, 2016)
We present a case of acute clenbuterol toxicity following ingestion of 20 μg of clenbuterol, resulting in symptoms of sympathetic activation, sinus tachycardia and electrolyte derangement. The patient was managed conservatively with fluid resuscitation, electrolyte replacement and monitoring, and discharged following a 5-day stay in hospital.